Neonatal diabetes mellitus due to a rare mutation in KCNJ11 gene - Kumar, Sunil; Thakur, Anuj (Indian Journal of Child Health, 2018)
Neonatal diabetes is a heterogeneous group of rare monogenic disorders with an incidence of about 1 in 100,000 live births presenting with in the first 6 months of life with polyuria, dehydration, and ketoacidosis. We, hereby, present a case of neonatal diabetes mellitus due to a very rare mutation (reported 1st time from Indian population) affecting the KCNJ11 gene encoding for KIR6.2 subunit of KATP channels resulting in inhibition of insulin release and hyperglycemia, leading to permanent neonatal diabetes for which sulfonylurea is the preferred treatment. Instead of insulin injection as endogenous insulin synthesis is not affected unlike other causes of permanent neonatal diabetes mellitus affecting insulin synthesis for which insulin is the only treatment.